2023
DOI: 10.1038/s41531-023-00517-w
|View full text |Cite
|
Sign up to set email alerts
|

Glucocerebrosidase activity and lipid levels are related to protein pathologies in Parkinson’s disease

Abstract: Parkinson’s disease (PD) and dementia with Lewy bodies (DLB) are progressive neurodegenerative diseases characterized by the accumulation of misfolded α-synuclein in the form of Lewy pathology. While most cases are sporadic, there are rare genetic mutations that cause disease and more common variants that increase incidence of disease. The most prominent genetic mutations for PD and DLB are in the GBA1 and LRRK2 genes. GBA1 mutations are associated with decreased glucocerebrosidase activity and lysosomal accum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…Accordingly, circulating glucosylsphingosine (GlcSph) is elevated in GD and PD patients [ 60 ]. A recent study showed GlcSph levels are raised in multiple brain regions in both idiopathic and GBA1 -linked PD patients, demonstrating a positive correlation with αSyn pathology [ 61 ]. GlcSph is formed by deacylation of GlcCer by the lysosomal enzyme acid ceramidase and high levels of this sphingolipid have been identified in nGD brains.…”
Section: Dysregulation Of Autophagic Pathways In Gba1 ...mentioning
confidence: 99%
“…Accordingly, circulating glucosylsphingosine (GlcSph) is elevated in GD and PD patients [ 60 ]. A recent study showed GlcSph levels are raised in multiple brain regions in both idiopathic and GBA1 -linked PD patients, demonstrating a positive correlation with αSyn pathology [ 61 ]. GlcSph is formed by deacylation of GlcCer by the lysosomal enzyme acid ceramidase and high levels of this sphingolipid have been identified in nGD brains.…”
Section: Dysregulation Of Autophagic Pathways In Gba1 ...mentioning
confidence: 99%
“…In PD patients, aberrant protein aggregation is the main pathogenic mechanism [ 80 ]. Mutations in leucine-rich repeat kinase 2 (LRRK2) lead to abnormal protein aggregation to form Lewy bodies [ 117 , 118 ], and the protein ratio of urinary exosome-phosphorylated LRRK2 (Ser(P)-129 LRRK2) to total LRRK2 is significantly increased in PD patients [ 119 ]. Plasma exosomal α-synuclein is increased in PD patients compared with healthy controls [ 8 ]; serum neuronal exosomal α-synuclein is significantly higher than in the APS group [ 9 ], and serum and plasma neuronal exosomal α-synuclein are significantly lower than in the multiple system atrophy (MSA) group [ 8 ].…”
Section: Exosomes In the Diagnosis Of Neurodegenerative Diseasesmentioning
confidence: 99%
“…The reduced GCase activity can be detected in the cerebrospinal fluid (CSF) and blood of GBA-PD patients [24][25][26], as well as in post mortem brain tissues [27]. In GBA-PD, GCase activity was the primary variable determining GlcSph levels which in turn shows a strong correlation with α-synuclein pathology in all brain areas other than the cerebellum, a brain region that does not exhibit PD pathology [27]. In vitro and in vivo models have been developed based on expression of pathogenic GBA1 mutants or administration of the GCase inhibitor conduritol β epoxide (CBE), to investigate the impact of reduced GCase levels on glycosphingolipid accumulation, lysosomal dysfunction, and increased α-synuclein aggregation [28,29].…”
Section: Introductionmentioning
confidence: 99%
“…Approximately 5-20% of PD patients carry a heterozygous GBA1 mutation (GBA-PD), differentiated by a 30-40% reduction in GCase activity, earlier disease onset including an increased risk for developing dementia with an up to five years earlier onset [12][13][14][15][16][17][18][19][20][21][22][23]. The reduced GCase activity can be detected in the cerebrospinal fluid (CSF) and blood of GBA-PD patients [24][25][26], as well as in post mortem brain tissues [27]. In GBA-PD, GCase activity was the primary variable determining GlcSph levels which in turn shows a strong correlation with α-synuclein pathology in all brain areas other than the cerebellum, a brain region that does not exhibit PD pathology [27].…”
Section: Introductionmentioning
confidence: 99%